Hato Point Acupressure Therapy on Reducing the Intensity of Dysmenorrhea in Adolescents - Az'zahra, Shabrina Frilia; Rianti, Emy; Nurhaeni, Heni (Poltekkes Kemenkes Semarang, 2025)
Background: dysmenorrhea has a high prevalence globally and nationally, yet it is often not managed optimally as it is considered a normal occurrence. Therefore, non-pharmacological management needs to be developed, one of which is through acupressure therapy. Acupressure is considered safer, more practical, and has fewer side effects compared to analgesics, and can be performed independently after proper education and training. Objective: this study aimed to determine the effect of Hato point acupressure therapy (Hegu LI4, Acupoint ST36, Taichong LV3, Sanyinjiao SP6) in reducing the intensity of dysmenorrhea in adolescents. Methods: this study employed a quasi-experimental design with a pretest-posttest approach and a control group. A total of 62 respondents were purposively divided into an intervention group and a control group, each comprising 31 respondents. The intervention was conducted over three consecutive days during menstruation, with a frequency of once per day, in two menstrual periods. Dysmenorrhea intensity was measured using the Numeric Rating Scale (NRS) before and after the intervention. Data were analyzed using the Wilcoxon test. Results: there was a significant decrease in average pain intensity in the intervention group compared to the control group (p-value < 0.005). The intervention group showed a consistent effect with a total pain reduction of 5.81 points in March and 5.49 points in April. Conclusion: Hato point acupressure therapy is effective in reducing dysmenorrhea intensity in adolescents and can be recommended as an independent nursing intervention.